Perbedaan Teknik Penanaman Terhadap Hasil Jumlah Koloni Bakteri Escherichia Coli Pada Suhu Inkubasi 36C: Perbedaan Teknik Penanaman Terhadap Hasil Jumlah Koloni Bakteri Escherichia Coli Pada Suhu Inkubasi 36C - RIZKY, VINCENTIA ADE (Jurnal FARMASIMED (JFM), 2019)
Escherichia coli bacteria are gram-negative bacteria in form of single or paired cells it is included Enterobacteriaceae family and intestinal normal flora. Laboratory tests conducted for the calculation of the number of germs can be done using cultivation techniques using a loop and micropipet. The aim of this research is to know the difference of number of bacteria bacteria on calibrated loop and micropipet to colony of Escherichia coli bacteria. This research is an analytical observation study with cross sectional design. The hypothesis was tested using independent t test with 95% confidence level. The results showed the average number colonies of Escherichia coli bacteria growing on PCA media using calibrated loop technique was 138,25 CFU/mL where as the average number of colonies of Escherichia coli bacteria grown on PCA media using micropipet technique was 104,56 CFU/mL, and significant value of p = 0,001. Furthemore, the result of data analysis showed that there were no any differences in the number of colonies of Escherichia coli bacteria in planting using calibrated loop technique and micropipet at incubation temperature of 36ÂºC.